The Effect of Profitability, Liquidity and Firm Size on Firm Value with Dividend Policy as a Moderating Variable - Rahmansyah, Moch. Fahrul; Musyaffi, Ayatulloh Michael; Widyastuti, Umi (Indonesian Journal of Advanced Research, 2025)
This study investigates the impact of profitability, liquidity, and firm size on firm value, with dividend policy serving as a moderating variable. The research focuses on energy sector companies listed on the Indonesia Stock Exchange (IDX) between 2018 and 2023. From a total of 83 listed firms, 17 were selected using purposive sampling for analysis. The study applies the Moderated Regression Analysis (MRA) technique and processes panel data using EViews version 13. The findings indicate that profitability significantly and positively influences firm value, whereas liquidity has a negative impact. Firm size also shows a significant positive effect on firm value. Although dividend policy does not have a significant direct effect on firm value, it does moderate the relationship between liquidity and firm value by strengthening it. However, it does not moderate the effect of profitability or firm size on firm value.